Antegrade Arterial and Portal Flushing Versus Portal Flushing Only for Right Lobe Live Donor Liver Transplantation—A Randomized Control Trial. Issue 4 (April 2018) - Pamecha, Viniyendra; Sandhyav, Rommel; Sinha, Piyush Kumar; Bharathy, Kishore Gurumoorthy Subramanya; Sasturkar, Shridhar
Abstract : Background: In live donor liver transplantation portal flush only of the graft is done on the bench. There are no data on antegrade arterial flush along with portal flush of the graft. Methods: Consecutive patients undergoing elective right lobe live donor liver transplantation were block-randomized to receive either portal flush only or both portal and antegrade arterial flush. The primary objectives were safety, rate of early allograft dysfunction (EAD), and impact on vascular and biliary complications. Results: After randomization, there were 40 patients in each group. Both groups had comparable preoperative, intraoperative, and donor variables. There were no adverse events related to arterial flushing. The portal and antegrade arterial flush group had significantly lower postoperative bilirubin on days 7, 14, and 21 (all P < 0.05), EAD ( P = 0.005), intensive care unit/high dependency unit ( P = 0.01), and hospital stay ( P = 0.05). This group also had lower peak aspartate aminotransferase ( P = 0.07), alanine aminotransferase ( P = 0.06) and lower rates of sepsis ( P = 0.08) trending toward statistical significance. Portal and antegrade arterial flush groups had lower ascitic fluid drainage and in-hospital mortality. Arterial and biliary complications were not statistically different in the 2 groups. Multivariate analysis of EAD showed portal with antegrade arterial flush was associated with lower rate ( P = 0.007), whereas model for end-stage liver disease Na ( P = 0.01) and donor age ( P = 0.03) were associated with a higher rate of EAD. Conclusions: Portal with antegrade arterial flushing of right lobe live liver grafts is safe, significantly decreases postoperative cholestasis, EAD, intensive care unit/high dependency unit, and hospital stay and is associated with lower rates of sepsis, ascitic drainage and inhospital mortality in comparison to portal flush only. Abstract : The authors conduct a randomized trial suggesting that antegrade perfusion of living donor liver grafts can improve perfusion and outcomes